THE EFFECT OF EXERCISES WITH THE METACOGNITIVE STRATEGY ACCORDING TO THE DAVIS MODEL TO LEARN SOME BASIC SKILLS IN FOOTBALL - Summer radi Bshara (Proximus Journal Publishing, 2025)
The importance of the research lies in using exercises according to the metacognitive strategy and demonstrating its effect on acquiring the skills necessary to perform the skills of rolling and scoring in football. As for the problem of the research, through the researcher's observation and follow-up, as a university teacher at Al-Ruwaimi Elementary School for Girls, of the systematic lessons that are limited to specific strategies, and for many reasons, she found weakness in the use of cognitive strategies, including the metacognitive strategy, according to specific models such as the Davis model, which facilitates the process of teaching basic skills for beginners in football, which works to establish the motor paths effectively, which directly affects the drawing of the motor program more accurately, which is consistent with new exercises, which increases the mechanism of learning these skills and attracts their attention during the lesson, and thus will affect the learning of skills to the fullest. As for the objectives of the research, the preparation of exercises according to the metacognitive strategy and the Davis model to learn the skills of rolling and scoring in football. And to identify the effect of exercises according to the metacognitive strategy and the Davis model to learn the skills of rolling and scoring in football for fifth grade students. The research community was represented by the fifth grade students of Al-Ruwaimi Elementary School for Girls. They were divided into two groups by lottery: the control group and the experimental group. Their number was (20) students for each group, and a survey group of (5) students for the survey experiments from sections (B-C) of the school. Thus, the percentage of the research sample was (58.27%). As for the conclusions, the strategy had a positive impact on the students’ learning of the skills under study. Using the (metacognitive strategy according to the Davis model) helps the teacher understand what the students individually require in order to understand the material. Using the exercises specific to the (metacognitive strategy according to the Davis model) showed the teacher the students’ strengths and weaknesses. As for the recommendations, the researcher recommends the need to pay attention to using modern strategies within the curriculum prepared for students in elementary schools. She also recommends the need to pay attention to diversifying the methods or teaching methods because individual differences are inevitable. And the need for the students to participate with the teacher in the process of giving the lecture As a kind of encouragement for them and to develop the personality of the students. Also by conducting various and different research on primary school students because they are the basis for learners and education
Keywords: encouragement; attention; strengths; recommendations